The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.7420
|View full text |Cite
|
Sign up to set email alerts
|

Reducing All-cause 30-day Hospital Readmissions for Patients Presenting with Acute Heart Failure Exacerbations: A Quality Improvement Initiative

Abstract: Background Congestive heart failure (CHF) is the most common cause of hospitalization in the US for people older than 65 years of age. It has the highest 30-day re-hospitalization rate among medical and surgical conditions, accounting for up to 26.9% of the total readmission rates. We conducted a quality improvement project at our hospital with the objective to reduce the 30-day all-cause readmissions of patients with CHF by improving the transition of care and setting up scheduled follow-up appointments withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Also, studies have shown significantly reduced all-cause mortality with more frequent vital sign measurements (more than twice a week). All-cause hospitalization rates and heart failure-related hospitalization rates are critical health economic indicators of patient discharge, transfer and post-discharge follow-up outcomes, and are helpful in assessing the prognosis of patients with CHF ( 33 ). The results of this study found that the e-health intervention group was able to significantly reduce all-cause hospitalization and heart failure-related hospitalization rates, with statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies have shown significantly reduced all-cause mortality with more frequent vital sign measurements (more than twice a week). All-cause hospitalization rates and heart failure-related hospitalization rates are critical health economic indicators of patient discharge, transfer and post-discharge follow-up outcomes, and are helpful in assessing the prognosis of patients with CHF ( 33 ). The results of this study found that the e-health intervention group was able to significantly reduce all-cause hospitalization and heart failure-related hospitalization rates, with statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our intervention incorporated elements that were informed by the PHCRP such as enhanced education on the evidence basis for reducing CHF readmissions [27][28][29][30] . Our work supports AHA guidelines recommending that CHF patients undergo routine SDOH screening 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Further research should focus on those pharmacologic, social, and lifestyle interventions that would decrease these rates, including ensuring scheduled followup appointments and patient education that have been shown to be effective for reducing the risk of being readmitted to the hospital during the first month after hospital discharge for acute myocardial infarction. 29…”
Section: Acute Clinical Complications Associated With Hospital Readmissionmentioning
confidence: 99%